Interferon-stimulated circHOMER1 attenuates antiviral innate immunity - Ao Zhang; Ranran Yao; Shijin Geng; Haiying Wang; Rong-Chun Tang; Hengxiang Yu; Rui Xu; Hong-Yan Chen; Yunxuan Zhou; Lan Zhang; Jun Zhang (mBio)
ABSTRACT In an initial screening of virus-induced differentially expressed circRNAs, circHOMER1 was significantly upregulated. However, its role in antiviral innate immunity remained unclear. circHOMER1 was upregulated in response to a range of stimuli, including RNA viruses, DNA viruses, as well as type I IFNs. Overexpression of circHOMER1 reduced the virus-induced type I IFN signaling pathway and promoted viral replication. Consistently, knockdown of circHOMER1 yielded opposite consequence. Mechanistically, circHOMER1 acted as a competitive endogenous RNA (ceRNA) for miR-145-3p, controlling the mRNA level of OTU domain-containing protein 7B (OTUD7B), thereby downregulating interferon regulatory factor 3 (IRF3) expression. Furthermore, circHOMER1 was found to disrupt the interaction between Ras GTPase-activating protein-binding protein 1 (G3BP1) and retinoic-acid-inducible protein I (RIG-I), impairing the detection of viral RNAs by RIG-I. Notably, the concordant immunosuppressive effects of circHOMER1 were observed in mouse infection models. These findings identify circHOMER1 as a novel interferon-stimulated circRNA that serves as a negative modulator of the antiviral innate immune response and is essential for immune homeostasis.IMPORTANCEA growing body of evidence suggests that circRNAs are involved in various physiological or pathological processes. Through circRNA microarray screening of virus-induced differentially expressed circRNAs, we identified an upregulated circRNA, circHOMER1. circHOMER1 is abundantly expressed in the brain. The known functions of circHOMER1 have been focused on the nervous systems and the related diseases. Its functions in the immune system are not discovered. In this study, we found that circHOMER1 is upregulated by viral infection, interferon treatment, etc. circHOMER1 can negatively modulate virus-induced type I IFN signaling by acting as a ceRNA or other mechanism. The regulatory function of circHOMER1 in innate immunity is critical for immune homeostasis. The dysregulation of circHOMER1 may be associated with virus encephalitis or other related diseases. circHOMER1 may be a potential therapeutic target of virus-induced infections and autoimmune diseases.